Renal Function Evaluation Following Donor Nephrectomy in Tertiary Kidney Transplant Center of Nepal - Gyawali, Milan; Luitel, Bhojraj; Pradhan, Manish Man; Chalise, Pawan Raj; Chapagain, Suman; Gyawali, Prem Raj (Journal of Institute of Medicine Nepal, 2024)
Introduction Live kidney transplant is the standard of care for patients requiring renal replacement therapy. Donors with increasing age and comorbid conditions such as obesity and hypertension are now included for transplant. This study was performed to evaluate the change in renal function of kidney donors over a period of one year. Methods This was an analytical study of patient’s who underwent donor nephrectomy from January 2022 to June 2023 at Department of Urology and Kidney Transplant Surgery, Tribhuvan University Teaching Hospital, Nepal. Renal function of donors in terms of serum creatinine, glomerular filtration rate, size of kidney and general physical examination including blood pressure pre-donation were compared with post donation period at three, six and twelve months. Results There were total of 76 cases available for analysis. Mean age of the donors was 44.6±10.1 years, ranging from 22 to 67 years, with male: female ratio of 1:2.45. There was no significant change in post donation blood pressure and kidney size. There was increase in serum creatinine level from baseline 70.47±14.96 to 93.20±17.61 (p<0.001) at three months follow up. Post donation glomerular filtration rate (GFR) of remnant kidney had increased significantly. Conclusion Post donation GFR of remnant kidney as well as serum creatinine level in live donor nephrectomy including the expanded criteria donors had increased significantly. Short-term deleterious effects in renal function post donation were not seen.